The Development and Testing of Balanced Communication Material for a Population-Based Breast Cancer Screening Program - De Nard, Francesca; Deandrea, Silvia; Bastiampillai, Anan Judina; Cavazzana, Laura; Carnevali, Davide; Principi, Niccolò; Luconi, Ester; Schulz, Peter Johannes; Castaldi, Silvana; Silvestri, Anna Rita (Frontiers in Communication, 2021)
Organized breast cancer screening (BCS) programs rely on written communication materials for achieving participation and informing women about screening-related benefits and limits. In order to achieve informed decisions and to maximize reader acceptance, the Agency for Health Protection of the metropolitan area of Milan aimed at improving the communication materials of the local BCS program through a multiphase, mixed-method process. Multidisciplinary working groups drafted three sets of materials: postal letters, an informative leaflet, and a question-and-answer online set. Readability was assessed using the Italian language-tailored GULPease index. Suitability and Comprehensibility were assessed using the SAM+CAM instrument. User perception was investigated through ‘think aloud’ interviews in two consecutive purposive samples. Participants’ intention to participate in the program was also assessed. After each phase was completed, materials were readapted, and previous phases were repeated, to maintain the pre-defined GULPease and SAM+CAM targets. During the quality improvement process, the overall mean GULPease and SAM+CAM scores increased from 65.5 (sd 10.4) to 67.7 (sd 8.2) and from 78 (sd 5.6) to 83 (sd 4.1), respectively. In light of the results of the first round of interviews, materials underwent rewriting and layout revision, which was generally appreciated during the second round, with a non-significant increase in the intention to participate in the program. However, negative emotions and miscomprehension concerning overdiagnosis were frequently reported, although less frequent in the second round, after rewording of the text. The mixed-method multistep process involving all the relevant key players allowed a balance among the multifaceted aspects of communication.